Fresh cow health issues - Jerry D. Olson (Kansas Agricultural Experiment Station Research Reports, 2003)
The post-calving period is a critical time in a cow's life. The first few weeks post-calving pose the highest risk period for a number of diseases including milk fever, mastitis, metritis, pneumonia, retained fetal membranes, ketosis, and displaced abomasum. Post-calving diseases adversely affect dry matter intake, peak milk production, and reproductive performance, in addition to increasing the risk of involuntary culling and death. Consequences of disease can be costly. The ideal strategy is to minimize losses associated with disease by preventing their occurrence. However, even with the best management practices in place, it is impossible to prevent all post-calving diseases. For cows that develop post-calving diseases, the challenge is to minimize losses by developing a strategy to identify them as early as possible, implementing effective treatment protocols, evaluating effectiveness of those protocols, and tracking incidence so preventive practices can be re-evaluated when the incidence exceeds a threshold level for an individual disease. A "fresh cow program" is an effective approach to systematically managing post-calving disease by close daily observation of cows during the first 10 to 14 days after calving. By conducting a brief, but systematic physical examination, including monitoring body temperature, disease can be identified as soon as possible and treatment protocols implemented. This approach minimizes losses associated with post-calving disease.; Dairy Day, 2003, Kansas State University, Manhattan, KS, 2003;
Keywords: Diary Day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-129-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 919; Dairy; Fresh cows; Health; Disease